Mycotoxin food safety risk in developing countries: food safety in food security and food trade - Bhat Ramesh V.; Vasanthi, Siruguri (International Food Policy Research Institute, 2003)
Mycotoxins are produced by fungi, commonly known as mold. These toxins can develop during production, harvesting, or storage of grains, nuts, and other crops. Mycotoxins are among the most potent mutagenic and carcinogenic substances known. They pose chronic health risks: prolonged exposure through diet has been linked to cancer and kidney, liver, and immune-system disease. Because mycotoxins occur more frequently under tropical conditions and diets in many developing countries are more heavily concentrated in crops susceptible to mycotoxins, these chronic health risks are particularly prevalent in developing countries.